2020
DOI: 10.1177/1055665620946980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three-Dimensional and Conventional Orthodontic Imaging Modalities for Localization of Impacted Maxillary Canines in Patients With Alveolar Cleft

Abstract: Objective: The purpose of this study was to identify which diagnostic parameters related to impacted maxillary canines can be reliably detected by the conventional orthodontic radiographic modalities and which factors need to be assessed by cone-beam computed tomography (CBCT). Design: In this cross-sectional study, 8 orthodontists evaluated 7 parameters related to the position and anatomy of the impacted canines by means of 2-dimensional (2D) records. After 1 month, the same process was repeated by means of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This finding implies that the lack of a periapical image in the current combination of imaging modalities did not significantly affect the diagnosis. 25 Padisar et al 21 reported a lower interobserver agreement for this parameter in patients with alveolar cleft. This finding could be attributed to the parameters that complicate a correct diagnosis in such patients such as impaired anatomy and superimposition of structures over the cleft site.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This finding implies that the lack of a periapical image in the current combination of imaging modalities did not significantly affect the diagnosis. 25 Padisar et al 21 reported a lower interobserver agreement for this parameter in patients with alveolar cleft. This finding could be attributed to the parameters that complicate a correct diagnosis in such patients such as impaired anatomy and superimposition of structures over the cleft site.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, another study advised the clinicians not to assess this parameter solely based on 2D images. 21 The lower accuracy of these 2D radiographic modalities for the assessment of this parameter could be attributed to projective displacement and geometric distortion. 23 The interobserver agreement for canine inclination in the current study was similar to the results of a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different malocclusions have also been a controversial risk factor for TMD (Manfredini et al, 2017 ; Salari et al, 2024 ). The diagnosis is based on clinical examinations, past medical and dental history, and paraclinical data (Daniele Kapos et al, 2020 ; Manfredini et al, 2023 ; Padisar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%